Planar cell polarity protein Celsr2 maintains structural and functional integrity of adult cortical synapses. (December 2022) - Li, Cunzheng; Wei, Ji-an; Wang, Diyang; Luo, Zhihua; Pang, Chaoqin; Chen, Kai; Duan, Juan; Chen, Bailing; Zhou, Libing; Tissir, Fadel; Shi, Lei; So, Kwok-Fai; et al.
Abstract: A few developmental genes remain persistently expressed in the adult stage, whilst their potential functions in the mature brain remain underappreciated. Here, we report the unexpected importance of Celsr2, a core Planar cell polarity (PCP) component, in maintaining the structural and functional integrity of adult neocortex. Celsr2 is highly expressed during development and remains expressed in adult neocortex. In vivo synaptic imaging in Celsr2 deficient mice revealed alterations in spinogenesis and reduced neuronal calcium activities, which are associated with impaired motor learning. These phenotypes were accompanied with anomalies of both postsynaptic organization and presynaptic vesicles. Knockout of Celsr2 in adult mice recapitulated those features, further supporting the role of Celsr2 in maintaining the integrity of mature cortex. In sum, our data identify previously unrecognized roles of Celsr2 in the maintenance of synaptic function and motor learning in adulthood. Highlights: Celsr2 facilitates cortical spinogenesis and cortico-striatal circuit activity in adult mice. Structural and functional maintenance of cortical synapse by Celsr2 contributes to complex motor skill learning. The molecular substrate of adult spinogenesis may consist in the potentiation of both presynaptic vesicles and postsynaptic densities by Celsr2.